Meta-analysis reveals significant association between FOXP3 polymorphisms and susceptibility to Graves' disease. Issue 4 (April 2021) - Tan, Guiqin; Wang, Xin; Zheng, Guangbing; Du, Juan; Zhou, Fangyu; Liang, Zhongzhi; Wei, Wenwen; Yu, Hongsong
Objective: This meta-analysis aimed to determine the associations between the rs3761547, rs3761548, and rs3761549 single-nucleotide polymorphisms (SNPs) of the forkhead box P3 ( FOXP3 ) gene and susceptibility to Graves' disease (GD). Methods: Case–control studies with information on the associations between the rs3761547, rs3761548, and rs3761549 FOXP3 SNPs and GD published before 01 May 2020 were identified in the PubMed, Embase, Web of Science, and China National Knowledge Infrastructure databases. Data from the studies were analyzed using RevMan version 5.3. Results: Seven independent case–control studies including 4051 GD patients and 4569 controls were included in the meta-analysis. The overall pooled analysis indicated that FOXP3 /rs3761548 and FOXP3 /rs3761549 polymorphisms were significantly associated with GD susceptibility (rs3761548: A vs. C, odds ratio [OR] = 1.32, 95% confidence interval [CI] 1.05–1.67; rs3761549: TT vs. CC, OR = 1.98, 95%CI 1.49–2.65; (TT + TC) vs. CC, OR = 1.44, 95%CI 1.11–1.88). In contrast, the FOXP3 /rs3761547 polymorphism was not associated with GD susceptibility. Subgroup analysis according to ethnicity showed that rs3761548 was associated with GD in Asians but not in Caucasians, whereas rs3761549 was associated in both Asians and Caucasians. Conclusion: This meta-analysis demonstrated that FOXP3 /rs3761548 and FOXP3 /rs3761549 SNPs were significantly associated with susceptibility to GD, at least in Asian populations.